(untitled) (Journal of Misan Researches, 2023)
This study attempted to reveal the characteristic of arrogance in ancient Arabic poetry, which is a feeling that controls a man and makes him adore himself. Thus, it is a very significant psychological concept in the psychoanalytic theory of the self. This study explained the most important reasons that prompted the poets to develop this feature in themselves, which is one of the behavioral psychological phenomena in which a man’s feeling of superiority conflicts with his feeling of inferiority or hides behind it. There were several reasons behind the emergence of this feeling in the two poets, and the most important among them was the issue of genealogy and the influence it had at that time, and to till today, in our Arab society. Furthermore, the environment had a great influence on the emergence of this feeling among the two poets, in addition to the circumstances surrounding them. The study presented poetic models related to what has been mentioned above. Finally, this study concluded that there is self- and collective arrogance in the two poets.